PRODUCTIVITY IN THE SERVICE SECTOR: A SERVICE CLASSIFICATION SCHEME FOR PRODUCTIVITY MEASUREMENT - Žemgulienė, Jolanta (Ekonomika, 2009)
The problem of service productivity discussed in the paper focuses on productivity measurement issues. The aim of the article is to elaborate criteria for the grouping of services as the reasoning for a deeper analysis of service productivity measurement. The research method is logical analysis of scientific literature. The criteria of customisation and tangibility of services have been suggested as a framework for productivity measurement interpretation.